Impact Assessment of Accreditation on Quality in Higher Education in Nigeria: The Study of North-East Geo Political Zone. - Amaechi, Appolus Azunwanne; Obiweluozor, Nkechi (NIU Journal of Humanities, 2021)
First generation universities in Nigeria were established between 1948 and 1962, subsequently; the National Universities Commission was established in 1962 and made a statutory body in 1974, to ensure academic standards and quality in Nigerian universities.  Before now, the products of these first generation universities were comparable to world-class standard in quality, but today, the song is that Nigerian universities are producing half-baked graduates. This paper examined the impact of accreditation on quality in Higher Education in Nigeria; vis-Ã -vis the five thematic areas covered by accreditation which are: academic content, staffing, physical facilities, funding and library. The descriptive survey research design was adopted. The population of the study consists of the 6 Federal Universities located in the North-East geo political zone of Nigeria. Simple stratified random sampling technique was used to select 30 respondents from each university and 60 respondents from the National Universities Commission (NUC).  In all 240 respondents were used in the study.  A 25-item researcher-developed Questionnaire titled â€œImpact of Accreditation on Quality in Higher Education Questionnaire (IAQHEQ)â€ served as major instrument for data collection. The instrument was validated by experts from the Faculty of Education, Taraba State University.  The reliability test conducted using Cronbach Alfa yielded a co-efficient index of 0.89. Five (5) research questions and one null hypothesis guided the study. Frequency counts, mean and standard deviation were used to answer research questions, while the t-test statistic was used to test the null hypothesis at 0.05 level of significance. Results of the finding reveal that accreditation has significant impact on quality in Higher Education in Nigeria, it also reveal that some universities resort to falsehood, borrowing of staff and equipment from other schools, to attract high score during accreditation which are not sustained; it reveal that facilities and library holdings improved tremendously through accreditation visits; It was concluded that periodic accreditation visit by the NUC is very important to maintain quality and standards in Nigerian universities. The paper therefore recommended among others, that universities in Nigeria must ensure a functional quality assurance directorate that will maintain the accreditation indices in relation to academic content, staffing, facilities, funding and library, in order to sustain quality and standards in Nigerian Universities. Keywords :  Impact Assessment, Accreditation, Quality, Higher Education.